Subpulmonary Obstruction Due to Aneurysmal Ventricular Septum in a Patient with Congenitally Corrected Transposition of the Great Arteries and Dextrocardia - Sheikh, Naveen; Banerjee, Sajal Krishna; Hossain, Md Zahid; Islam, Md Tariqul; Karim, Tahmina; Hasan, Atm Iqbal; Adhikary, Dipal Krishna; Hasan, Md Nazmul; Hoque, Md Harisul (University Heart Journal, 2015)
Congenitally corrected Transposition of Great Arteries is usually associated with multiple cardiac defects. Morphologic left-ventricular outflow (pulmonary) tract obstruction due to aneurysm of the membranous ventricular septum in patients with corrected transposition and ventricular septal defect is rare, but was reported in the past. This is even more uncommon in patients with dextrocardia, prompting us to document this case. Absence of the conus with resultant proximity of the aneurysm to the subpulmonary region and higher pressures in the left-sided morphologic right ventricle lead to obstruction of outflow tract in corrected transposition. Echocardiogram with Doppler interrogation and cardiac catheterization with selective cineangiography are the diagnostic tests of choice. Surgical resection of the aneurysm with patch closure of ventricular septal defect, avoiding injury to the conduction system, is recommended. University Heart Journal Vol. 10, No. 1, January 2014; 31-38